(untitled) (Research, Society and Development, 2022)
The expansion of agricultural frontiers and the indiscriminate use of land make it urgent to establish measures that are proven to be effective for the legal monitoring of land use and land cover. The development of studies with the application of geotechnologies such as geoprocessing and remote sensing has shown significant results, especially with regard to the application of methodologies for the follow-up and monitoring of large areas. Thus, this research aimed to analyze the use and land cover in the area of ​​the Parque Nacional das Nascentes do Rio Parnaíba, from 1990 to 2020, using data from the MapBiomas platform, where the acquired data were processed through the software QGIS, resulting in information in which it was possible to make a diagnosis of land use and cover and, subsequently, to make maps and statistical data. The results showed that, in 1990, there was no cultivation in the area inside the park and in its surroundings. However, in the following years, the existence of crops increased for each year analyzed, reaching more than 3 thousand hectares inside the park and more than 22 thousand hectares in its surroundings for the year 2020. The methodology applied proved to be efficient, since it presented information that may be useful for the decision-making of the competent bodies, providing a basis for the elaboration of policies aimed at the protection and sustainable development of the Park.